Cohomology with Lp-bounds on polycylinders - P. W. Darko; C. H. Lutterodt (International Journal of Mathematics and Mathematical Sciences)
Let Ω=Ω1×…×Ωn be a polycylinder in ℂn, that is each Ωj is bounded, non-empty and open in ℂ. The main result proved here is that, if Bp is the sheaf of germs of Lp-holomorphic functions on Ω¯ then Hq(Ω¯,Bp)=0 for q≥1. The proof of this is then used to establish a Leray's Isomorphism with Lp-bounds theorem.